Type II- Pleuropulmonary Blastoma: A case report - Saeed, Mohammed S.; Yahya, Thukaa T.; kareem, Wasna'a A.; Hudder, Osama E. (Journal of the Faculty of Medicine Baghdad, 2011)
Pleuropulmonary blastoma is a rare and aggressive neoplasm typically presents in young children, younger than 5 years, as a pulmonary and/or pleural-based tumor. We reported a case of type-II pleuropulmonary blastoma (PPB) in an 8 month old infant who presented to Al-Khansa'a Maternity Hospital in Western Mosul with a history of repeated attacks of shortness of breath and signs of pulmonary infection unresponsive to treatment. A bronchoscopic examination showed a mass involved and obstructed the orifice of the main bronchial tree of the right upper lung lobe. A thoracotomy was performed; tumor involved the right upper lung lobe, the covering pleural surface and invading the mediastinal structures. Right upper lobectomy was performed. Tumor had cystic and solid components. It characterized histologically by a mixture of primitive blastematous and sarcomatous elements.